2016
DOI: 10.1021/acs.molpharmaceut.5b00387
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Aggregation Kinetics of a Therapeutic Antibody Fragment

Abstract: The analytical characterization of biopharmaceuticals is a fundamental step in the early stages of development and prediction of their behavior in bioprocesses. Protein aggregation in particular is a common issue as it affects all stages of product development. In the present work, we investigate the stability and the aggregation kinetics of A33Fab, a therapeutically relevant humanized antibody fragment at a wide range of pH, ionic strength, and temperature. We show that the propensity of A33Fab to aggregate u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 64 publications
(119 reference statements)
7
102
0
Order By: Relevance
“…After the expression of designed variants, their conformational stability was assessed through different thermal stability measures. We selected a formulation condition of 1 mg/ml Fab in 20 mM sodium citrate, pH 4, at an ionic strength of 200 mM, as this partially unfolded the wild-type protein at 65 °C by 6% 36 , and to led to aggregation on a practical timescale. These conditions were used for both thermal stability measurement and aggregation kinetics.…”
Section: Thermal Stability Measurement For Tm Ton and Fraction Of Unmentioning
confidence: 99%
See 2 more Smart Citations
“…After the expression of designed variants, their conformational stability was assessed through different thermal stability measures. We selected a formulation condition of 1 mg/ml Fab in 20 mM sodium citrate, pH 4, at an ionic strength of 200 mM, as this partially unfolded the wild-type protein at 65 °C by 6% 36 , and to led to aggregation on a practical timescale. These conditions were used for both thermal stability measurement and aggregation kinetics.…”
Section: Thermal Stability Measurement For Tm Ton and Fraction Of Unmentioning
confidence: 99%
“…Previously, the A33 Fab was studied across a wide range of pH, ionic strength and temperature 36 . It was found that the aggregation rates could only be correlated well with thermal transition temperatures (Tm) at an elevated incubation temperature of 65 °C, while the correlations dropped substantially at 4-45 °C, consistent with previous observations on IgG variants 37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in accelerated and innate aggregation propensities (Goldberg et al, 2017) may arise because the acceleration method increases the relative flux through certain pathways which are distinct to those traversed during production or upon storage (Chakroun, Hilton, Ahmad, Platt, & Dalby, 2016; Luo et al, 2011; Phillips et al, 2017; van der Kant et al, 2017). There is thus a need to develop stress tests that more closely replicate the conformational ensemble generated during processing and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Native protein conformations are only marginally stable, and are highly dynamic, hence they are more realistically described as a native ensemble. There is increasing evidence to suggest that under native conditions, aggregation takes place primarily from partially unfolded native-like states [812]. However, little is known about the structures of native conformers that initiate aggregation, or how these are affected by different stress conditions.…”
Section: Introductionmentioning
confidence: 99%